Origin and early history of the Muslims of Keralam, 700 A.D.-1600 A.D. - More, J. B. P. (Other Books, 2011)
onceived as the sixth title in the series of Mappila studies, this book is a narrative on Kerala Muslims who have only rarely been chronicled in English . The book has many issues in its focus; the origin and evolution of the Kerala Muslims until 1600 AD, the historical background of Malabar before the advent of Islam, the origin and evolution of Islam in Malabar from 700 AD to 1500 AD, the legend of Cheraman Perumal and finally Vasco Da Gama's arrival on the Malabar Coast and its consequences in various quarters